Praktik Tahfiz Al-Qur’an selama Masa Pandemi COVID-19 (Studi Living Qur’an di SD Islam Al Azhar 17 Bintaro) - Muhammad Yusuf; Isnawati Isnawati (JOURNAL OF QUR'AN AND HADITH STUDIES, 2023)
This study describes the practice of tahfiz Al-Qur'an during the pandemic period at SD Islam Al Azhar 17 Bintaro. This research is qualitative research using field research data collection methods. The primary data source was the Learning Syllabus for Tahfiz Al-Qur'an at SD Islam Al Azhar 17 Bintaro, the results of observations, interviews, and findings during the research. The secondary source is authoritative literature which examines the tahfiz program during the pandemic. This research shows that during the pandemic, the daily agenda and supporting activities for the practice of reciting the Qur'an at SD Islam Al Azhar 17 Bintaro continued to run well, even with changes and adjustments. The talaqqi pattern, which was originally carried out in person, changed to virtual through the Zoom application and WhatsApp video calls. In implementing tahfiz with the Distance Learning (PJJ) system, teachers and schools must be able to establish good synergy with parents, because the role of parents has a significant impact on the achievement of student memorization.